Effects of Culture Media on Viability of Beauveria Bassiana and Its Pathogenicity Against Coffee Bean Borer (Hyphotenemus Hampei) - Brotodjojo, R.R. Rukmowati; Solichah, Chimayatus; Widyaningtyas, Anindita; Wicaksono, Danar (Proceeding International Conference on Science and Engineering, 2020)
Coffee bean borer (Hypothenemus hampei) attacks coffee when it is still in the plantation until it is in the storage that reduce the quality of coffee. To avoid the negative impact of chemical insecticides, biological control is carried out by using entomopathogen Beauveria bassiana. The aims of this research were to study the effects of culture media on viability of B. bassiana and its pathogenicity in controlling H. hampei. Laboratory experiment was arranged in Completely Random Design (CRD). This research used 8 (eight) treatments namely KO: Distilled water, Kk: Lamda Sihalothrin 25 EC (Chemical Insecticide), B1: 10 g/L B. bassiana cultured in rice bran media, B2: 20 g/L B. bassiana cultured in rice bran media, B3: 30 g/L B. bassiana cultured in rice bran media, B4: 10 g/L B. bassiana cultured in corn media, B5: 20 g/L B. bassiana cultured in corn media and B6: 30 g/L B. bassiana cultured in corn media. Each treatment was applied on coffee beans infested with 20 H. hampei and repeated 4 (four) times. The results showed that rice bran media produced the highest number of spores with highest viability. The application of B. bassiana could killed H. hampei. The concentration of 30 g/L of B. bassiana cultured in rice bran media resulted in the fastest mortality (Mortality time and Lethal Time 50%) of H. hampei.